Radiographic cardiac indices for the evaluation of cardiac and left atrial sizes in healthy Wistar albino rats (Rattus norvegicus) - ÇETİNKAYA, Mehmet Alper; KAYA, Mahir (The Thai Journal of Veterinary Medicine, 2022)
This study was performed for the purpose of comparing vertebral heart score (VHS), radiographic left atrial dimension (RLAD) and vertebral left atrial size (VLAS) values derived from plain and contrast right lateral thoracic radiographs from 70 healthy, young adult Wistar albino rats and to identify reference values for these radiographic cardiac indices. Measurements were taken by two observers blinded to the study data. VHS, RLAD and VLAS median values and reference ranges were 8v and 7-9.3v for plain radiography, 8.2v and 7.4-9.5v for contrast radiography (P< 0.000), 1.3v and 1-1.8v for plain radiography, 1.3v and 1.1-1.6v for contrast radiography (P <0.000) and 1.9v and 1.4-2.4v for plain radiography and 1.95v 1.5-2.4v for contrast radiography (P<0.001), respectively. The only statistically significant difference was observed in terms of gender between VHS values from plain and contrast radiographs (P<0.02). Intraobserver and interobserver measurements revealed excellent agreement for radiographic cardiac indices obtained from contrast radiography. The study measurements indicate that contrast radiography provides a more effective quantitative assessment of cardiac and left atrial sizes than plain radiography. The radiographic cardiac index measurements presented in this study can serve as a reference baseline for both veterinarians and experimental cardiovascular studies.